A literature review assessing whether behaviour change interventions aimed at young people aged 16 to 24 years altered their sexual risk taking behaviours - Tierney, Charlotte (2010)
Introduction and background Rationale for topic selection This dissertation will investigate behaviour change interventions regarding sexually transmitted infections (STIs) in young people aged 16 to 24 years and identify how these interventions are undertaken in an attempt to promote safe sex by increasing condom use consistency and increasing education and knowledge about STIs. The purpose of completing a literature review is to ascertain what information on the subject already exists, which can help to provide a foundation for recommending and implementing high quality care in future practice developments. A literature review is the best way to investigate this topic, as it outlines the need for further research about a subject, and prevents any repetition of mistakes from previous research undertaken (Hek et al, 2000; Garrard, 2007). A review of the literature consists of finding the appropriate subject materials, reading the information, analysing the findings and summarising the results about the topic (Hek et al, 2000; Garrard, 2007; Hart, 2001; Hek and Moule, 2006). By reviewing the interventions that have been undertaken, assessments of any further actions needed to increase young people’s knowledge and attitudes of STIs and HIV, increase their condom use consistency, and inform them about protecting themselves from STIs and HIV, can be made. Once the review is completed, recommendations for further research and interventions that are needed will be discussed.